Bombers B-52 [videorecording (DVD)] - Douglas, Gordon, 1907-1993; Wood, Natalie; Malden, Karl; Hunt, Marsha, 1917-; Zimbalist, Efrem, Jr., 1918-2014 (Warner Home Video, 2009)
Ever since a run-in during the Korean War, grizzled airplane mechanic Sgt. Chuck Brennan has disliked hotshot pilot Col. Jim Herlihy. Brennan has a new reason to be ticked off: Helihy is dating his daughter. Central to Cold War-era preparedness is the new airship they're putting through a key test run: the 200-ton B-52 Stratofortress. There is no room for animosity, because on this flight, danger rides the skies.